Looking from the Organisational Learning lens at technology enabled HR in Indian organisations. (5th February 2007) - Bhatnagar, Jyotsna
In some Indian organisations we find a mature, transformational, decision analytics based Human Resource Information System (HRIS), while in most organisations it remains a transactional process. The current study reflects on how OL capability (from here onwards organisational learning will be referred as OL) is enhanced by these systems and explores the implementation and design of these systems in India. Some organisations have implemented the Human Resource (HR) architecture through the technology driver. Analysis in terms of type of learning need, IT impact, level of Learning, role of HR and need analysis has been conducted for three case studies. The paper explores further research implications.